Estudio de factibilidad para la creación de una empresa destinada a comercializar productos corporativos, fabricados a base de material biodegradable, en la ciudad de Armenia. (2013)
The project creates biodegradable products, specifically agendas, cups, and pens, and provide solutions to environmental pollution of our planet, affected by phenomena such as overexploitation of ecosystems, the greenhouse effect, the destruction of the ozone layer, emission of polluting gases into the atmosphere, accumulation of organic waste material is difficult to degrade, adversely affecting nature, creating more pollution, the use of toxic products. Knowing the dire nature of the toxins, the project creates effective quality biodegradable items with a corporate design, an image, a logo, a name, a brand, a vision, mission, objectives, commercial impact, dissemination and positioning the market, satisfying the needs of customers, revolutionizing the techniques of manufacture of environmentally friendly materials and recyclable, easy degradation, generating jobs, and dividends for the company, being a leader in manufacturing biodegradable items, creating awareness of using products ecological, reducing the use of items such as plastics, biodegrables not being dangerous to the flora and fauna of our country. The project is in the Quindío Armenia, are professionals in business administration, economics, international business administration, public accounting, and establish partnerships with customers, suppliers, salespeople, secretaries, messengers, distributors, for the project will have a hand profitable work, physical facilities, and modern infrastructure, buy raw materials, office equipment, to manufacture biodegradable products, the company is legal, we will conduct marketing and advertising strategies, project feasibility studies, scale models will use fliers, the Internet , radio spots, and television shows to publicize the product, to attract customers, polls, surveys, free samples, promotions, tastings, financial statements, budgets, interviews, experimental tests, the acceptance of the consumer, contributing to socio-economic development of our region.